Association of angiotension-converting enzyme gene I/D polymorphism with athletic performance in elite strength athletes - Zhao, Y.; Zhang, W.; Ma, L. (2001)
The aim of the present study is to examine the association between the ACE gene I/D polymorphism with cardiac structure and function, body composition and anaerobic capacity and power in Chinese elite power athletes. Twenty male athletes (age: 20±3.15,mean±SD) volunteered to participate in this study. The cardiac structure and function of the subjects were measured by M-mode echocardiography, body composition determined by bioelectrical impedance and anaerobic capacity and power as well as blood lactates after all-out exercise tested with modified Wingate method. Genomic DNA was extracted from 1ml sterile 0.9% saline mouthwash sample and ACE genotype was classified by using a three-primer PCR amplification developed by Evans, et al. 30 cycles of amplification were performed with PE-9600. Amplification products were visualized after electrophoresis in 4% agarose gel with EB staining. The results indicated that the ACE gene D and I allelic frequency in athletes was not similar with normal population. The I allele frequency was significantly higher in athletes (P< 0.05). Further analysis demonstrated that significant difference was found in LVM/BSA between the homozygotes II and DD and between DD and heterozygotes ID (P<0.01). Significant difference was also observed in peak BLa during Wingate test between II and DD and between ID and DD (P<0.01). However, no association was shown between the ACE I/D polymorphism and estimates of BMI, body fat content, PAP/kg (peak anaerobic power) and AAP/kg (averaged anaerobic power). Based on these results, we concluded that the ACE gene I allele might be a genetic mark associated with elite performance among the highly trained Chinese power athletes.